A geometric decomposition of spaces into cells of different types II: Homology theory - Minian, Elias Gabriel (2008)
We develop the homology theory of CW (A)-complexes, generalizing the classical cellular homology theory for CW-complexes. A CW (A)-complex is a topological space which is built up out of cells of a certain core A.